(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
يقوم هذا البحث على متابعة بعض الأعمال التي قام بها مجموعة من الباحثين [11-8]وذلك خلال دراسة كلٍ من العزم المغناطيسي للنيوترينو وعوامل الصيغة الكهرطيسية المعرفة له والعلاقة بين هذه المعاملات جميعاً الناتجة عن : أ) التفاعل الضعيف والمغناطيسي للنيوترينو (للنيوترينو المضاد) - الكترون في التشتت المرن ، ب) التفاعل الضعيف والكهرطيسي للنيوترينو (للنيوترينو المضاد) - إلكترون في التشتت المرن ، ج) انحراف كتلة النيوترينو عن الصفر في هذه التفاعلات بعيدا عن النموذج المعياري للتفاعل الضعيف غلاشو- واينبرغ - سلام ، د) تفاعل التيارات المشحونة والتيارات الحيادية في التشتت المرن للنيوترينو (للنيوترينو المضاد) - الكترون. تم الحصول أخيرا على علاقة هامة بين عوامل الصيغة الكهرطيسية للنيوترينو والعزم المغناطيسي له. This research looks at some works of researchers [8-11] and investigates magnetic moment of neutrino, electromagnetic form factors of neutrino and the relationship among all these parameters, caused by the: a) weak and magnetic neutrino (antineutrino)-electron interaction in elastic -scattering; b) weak and electromagnetic neutrino (antineutrino)-electron interaction in elastic -scattering; c) deviation of the neutrino mass from zero in these processes, far from the standard electroweak interaction model of Glashow-Weinberg-Salam (GWS); d) interaction of charged currents (CC) and neutral currents (NC) in elastic electron-neutrino (antineutrino) scattering. Finally an important relation between the electromagnetic form factors of neutrino and magnetic moment of neutrino was obtained.